Cover Image. (20th August 2020) - Li, Bo; Wang, Chong; Yuan, Xiaohong; Wang, Zhen; Kim, Kyojin; Li, Jinzhong; Cheng, Aoming; Han, Zhengxue; Feng, Zhien
Abstract : The cover image is based on the Original Article Is it necessary to receive radiation for pT3‐4N0 oral cancer without other adverse risk features? by Zhien Feng et al., https://doi.org/10.1111/odi.13336 .